South Asian (Clade I) Candida auris meningitis in a paediatric patient in Iran with a review of the literature. Issue 2 (27th November 2021) - Mirhendi, Hossein; Charsizadeh, Arezou; Aboutalebian, Shima; Mohammadpour, Masoud; Nikmanesh, Bahram; de Groot, Theun; Meis, Jacques F.; Badali, Hamid
Abstract: Candida meningitis is a rare life‐threatening yeast infection mostly involving immunocompromised or paediatric patients undergoing neurosurgical procedures or shunt placement. Due to difficulties in diagnosis because of diverse clinical manifestations, the number of patients affected is most likely underestimated. Therefore, the correct diagnosis may be delayed for months, and accurate species identification is highly recommended for administering appropriate antifungal therapy. We report the first case of fluconazole‐resistant Candida auris meningitis in a paediatric patient in Iran. This strain was probably imported, as it genotypically belonged to Clade I from South Asia. Furthermore, we include a literature review of C auris meningitis cases, as the number of cases with C auris meningitis has increased with reports from the United Kingdom, India and Iran. This problem might increase further in the era of COVID‐19 due to attrition of experienced healthcare personnel and a high workload of hospital healthcare workers. To understand the precise prevalence of this emerging multidrug resistance pathogen, epidemiological surveillance studies are urgently warranted.